Pre-stimulus EEG Microstates Correlate With Anticipatory Alpha Desynchronization - Spadone, Sara; Croce, Pierpaolo; Zappasodi, Filippo; Capotosto, Paolo (Frontiers in Human Neuroscience, 2020)
In the last decades, several electrophysiological markers have been investigated to better understand how humans precede a signaled event. Among others, the pre-stimulus microstates’ topography, representing the whole brain activity, has been proposed as a promising index of the anticipatory period in several cognitive tasks. However, to date, a clear relationship between the metrics of the pre-stimulus microstates (i.e. the global explained variance and the frequency of occurrence) and well-known EEG marker of the anticipation (i.e. the alpha power reduction) has not been investigated. Here, after extracting the microstates during the expectancy of the semantic memory task, we investigated the correlations between the microstates features and the anticipatory alpha (8-12 Hz) power reduction (i.e. the event related de-synchronization of the alpha rhythms; ERD), that is widely interpreted as a functional correlate of brain activation. We reported a positive correlation between the occurrence of the dominant, but not non-dominant, microstate and both the mean amplitude of high-alpha ERD and the magnitude of the alpha ERD peak, so that the stronger the decrease (%) in the alpha power-ERD the higher the frequency of occurrence of the dominant microstate. Moreover, we found a positive correlation between the occurrence of the dominant microstate and the latency of the alpha ERD peak, suggesting that subjects with higher frequency of occurrence present the stronger alpha ERD closely to the target. These correlations were not significant between the global explained variance and all anticipatory alpha ERD indices. Our results suggest that only the occurrence of the dominant, but not non-dominant, microstate should be considered as a useful electrophysiological correlate of the cortical activation.